Mesoporous magnesium silicate-incorporated poly(ε-caprolactone)-poly(ethylene glycol)-poly(ε-caprolactone) bioactive composite beneficial to osteoblast behaviors - Niu, Yunfei (Dove Medical Press, 2014)
Mesoporous magnesium silicate (m-MS) and poly(ε-caprolactone)-poly(ethylene glycol)-poly(ε-caprolactone) (PCL-PEG-PCL) composite (m-MPC) was synthesized by solvent casting method. The results suggest that the mechanical properties of compressive strength and elastic modulus, as well as hydrophilicity, of the m-MPC increased with increase of m-MS content in the composites. In addition, the weight loss of the m-MPC improved significantly with the increase of m-MS content during composite soaking in phosphate-buffered saline for 10 weeks, indicating that incorporation of m-MS into PCL-PEG-PCL could enhance the degradability of the m-MPC. Moreover, the m-MPC with 40 w% m-MS could induce a dense and continuous apatite layer on its surface after soaking in simulated body fluid for 5 days, which was better than m-MPC 20 w% m-MS, exhibiting excellent in vitro bioactivity. In cell cultural experiments, the results showed that the attachment and viability ratio of MG63 cells on m-MPC increased significantly with the increase of m-MS content, showing that the addition of m-MS into PCL-PEG-PCL could promote cell attachment and proliferation. The results suggest that the incorporation of m-MS into PCL-PEG-PCL could produce bioactive composites with improved hydrophilicity, degradability, bioactivity, and cytocompatibility.